Fast image encryption algorithm with random structures - Etem, Taha; Kaya, Turgay (Taylor and Francis Ltd., 2023)
Block encryption algorithms are among the most preferred applications in cryptographic systems. Block ciphers should have accomplished some requirements for a secure communication system. They should be evaluated in terms of cryptanalysis methods for widespread usage. The aim of this paper is to introduce a new secure and fast block encryption algorithm for images. For this purpose, a new block cipher, which offers an innovative encryption structure for key generation systems and can use S-boxes with different methods, is proposed. A Dynamic S-Box is used in the algorithm for both substitution and key generation purposes. Linear and differential cryptanalysis methods were performed successfully. UACI and NPCR tests show that the proposed symmetric block cipher algorithm is compatible with image encryption systems. The 512-bit key length provides the highest security for block encryption. Additionally, information entropy test, correlation coefficients, mean-squared error, and peak signal-to-noise ratio analyses were concluded successfully. The novelty of the paper is building a cryptanalysis attack-resistant block cipher algorithm that presents a lightweight cryptographic solution for image encryption systems. © 2023 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Block cipher; image processing; NPCR and UACI; S-Box; symmetric encryption